Respostas

2014-08-17T12:29:34-03:00
Vamos lá:

f(-1) = -4

f(-1) = a.(-1)² + b.(-1) + c

f(-1) = a - b + c

Como f(-1) = -4:

-4 = a - b + c

f(1) = 2

2 = a + b + c

Somamos o que encontramos:

a - b + c = -4
a + b + c = 2
2a + 2c = -2 (÷2)

a + c = -1

f(2) = -1

-1 = 4a + 2b + c

Como temos que a + c = -1, podemos dizer que c = -1-a

Logo:

-1 = 4a + 2b + (-1-a)
-1 = 4a - a + 2b -1

3a + 2b = 0

e temos que:

2 = a + b + c
2 = a + b + (-1 - a)
2 = a - a + b - 1
Logo:

b = 3

Substituímos:

3a + 2b = 0

3a + 6 = 0
3a = -6

a = -2

e também:

c = -1-a
c = -1 -(-2)
c = 1



 Logo, \ \boxed{f(x)=-2x^2+3x+1}
7 4 7